2019
DOI: 10.3390/toxins11090490
|View full text |Cite
|
Sign up to set email alerts
|

TMA, A Forgotten Uremic Toxin, but Not TMAO, Is Involved in Cardiovascular Pathology

Abstract: Trimethylamine-N-oxide (TMAO) has been suggested as a marker and mediator of cardiovascular diseases. However, data are contradictory, and the mechanisms are obscure. Strikingly, the role of the TMAO precursor trimethylamine (TMA) has not drawn attention in cardiovascular studies even though toxic effects of TMA were proposed several decades ago. We assessed plasma TMA and TMAO levels in healthy humans (HH) and cardiovascular patients qualified for aortic valve replacement (CP). The cytotoxicity of TMA and TMA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
96
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(103 citation statements)
references
References 39 publications
5
96
0
2
Order By: Relevance
“…Gut microbiota-derived metabolites TMAO, TMA, and DMA from dietary methylamines have recently gained much attention due to their high association with CV risk [8][9][10]29,30]. In the present study, our results are consistent with previous reported data in CKD adults [31,32], showing that TMAO is increased in CKD with a weak inverse correlation (r = −0.283) between plasma TMAO level and eGFR.…”
Section: Discussionsupporting
confidence: 92%
“…Gut microbiota-derived metabolites TMAO, TMA, and DMA from dietary methylamines have recently gained much attention due to their high association with CV risk [8][9][10]29,30]. In the present study, our results are consistent with previous reported data in CKD adults [31,32], showing that TMAO is increased in CKD with a weak inverse correlation (r = −0.283) between plasma TMAO level and eGFR.…”
Section: Discussionsupporting
confidence: 92%
“…Recent evidence reveals microbiota-derived metabolites TMAO and TMA related to cardiovascular disease [16,17], with not always consistent results [43]. Given that dietary factors are associated with plasma concentrations of TMA [16] and that TMAO level is controlled by its synthesis and metabolism, simultaneously measures of the TMAO-to-TMA ratio and the DMA-to-TMAO ratio were expected to reflect a cumulative state of TMAO. In the current study, perinatal HF diet caused the increases of TMA levels in adult offspring.…”
Section: Discussionmentioning
confidence: 99%
“…The investigation conformed to the Institutional Animal Care and Use Committee of Kaohsiung Chang Gung Memorial Hospital (permit #201721408) that complies with the Guide for the Care and Use of Laboratory Animals of the National Institutes of Health. Twelve virgin Sprague Dawley (SD) rats (12)(13)(14)(15)(16) weeks old) were purchased from BioLASCO Taiwan Co., Ltd. (Taipei, Taiwan). Rats were housed under 12-h light/12-h dark conditions with a relative humidity of 55% in an Association for Assessment and Accreditation of Laboratory Animal Care International (AAALAC)-approved animal facility in our hospital.…”
Section: Animal Modelmentioning
confidence: 99%
See 2 more Smart Citations